2021
DOI: 10.1007/s10565-021-09649-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 protects cardiomyocytes against doxorubicin-induced cardiotoxicity by inhibiting P53/Fas-dependent cell death and augmenting endogenous antioxidant defense mechanisms

Abstract: Sirt6, a class III NAD + -dependent deacetylase of the sirtuin family, is a highly speci c H3 deacetylase and plays important roles in regulating cellular growth and death. The induction of oxidative stress and death are the crucial mechanisms involved in cardiomyocyte damage and cardiac dysfunction in doxorubicininduced cardiotoxocity, but the regulatory role of Sirt6 in the fate of DOX-impaired cardiomyocytes is poorly understood. In this study, we exposed heterozygous Sirt6 knockout (Sirt6 +/− ) mice and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Its expression and activity are up‐regulated in various myocardial diseases, including myocardial infarction, hypertrophic cardiomyopathy, DCM, etc 110 . SIRT6 inhibits apoptosis/necrosis by being recruited into the promoter region of target genes Fas and FasL by p53, reducing histone acetylation and inhibiting the transcriptional activity of p53 69 . Interestingly, the protection of SIRT6 on cardiomyocytes also involves the activation of AMPK pathway.…”
Section: Role Of Sirt6 In Dcm Cell Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression and activity are up‐regulated in various myocardial diseases, including myocardial infarction, hypertrophic cardiomyopathy, DCM, etc 110 . SIRT6 inhibits apoptosis/necrosis by being recruited into the promoter region of target genes Fas and FasL by p53, reducing histone acetylation and inhibiting the transcriptional activity of p53 69 . Interestingly, the protection of SIRT6 on cardiomyocytes also involves the activation of AMPK pathway.…”
Section: Role Of Sirt6 In Dcm Cell Processmentioning
confidence: 99%
“…90,91 Studies have found that SIRT6 can reduce myocardial oxidative stress damage caused by excessive ROS production by up-regulating endogenous antioxidant levels, and further inhibit p53 transcriptional activity by reducing histone acetylation, thus protecting the heart from diabetes-induced cardiomyopathy. 69 Specific deletion of SIRT6 can induce mitochondrial oxidative dysfunction and glycolipid toxicity in cardiomyocytes, which leads to myocardial hypertrophy and fibrosis. 32 In SIRT6 KO diabetic model mice, the mRNA levels of major genes involved in fatty acid biosynthesis (such as FAS and SCD1) were significantly upregulated, and the expression of cardiac fatty acid transporters and lipid accumulation in cardiomyocytes were significantly increased; on the contrary, the fatty acid uptake of cardiomyocytes in diabetic mice overexpressed with SIRT6 is reduced, which indicates that SIRT6 can protect cardiac structure and function by regulating the uptake and utilization of fatty acids in cardiomyocytes and maintaining the balance of fatty acid metabolism.…”
Section: Maintaining Mitochondrial Homeostasis and Regulating Lipid M...mentioning
confidence: 99%
“…MiR-195 is upregulated in human cardiomyocyte cell lines by DOX treatment, and it might promote cardiomyocyte apoptosis targeting Bcl-2 and SIRT3 (Zhang et al, 2018;Chen et al, 2019a). SIRT6 attenuates DIC by upregulating endogenous antioxidant levels and attenuating apoptosis (Wu et al, 2021). The latter is achieved by SIRT6 interaction with p53, which leads to the repression of p53 transcription and binding to the Fas/FasL promotor region to reduce apoptotic signaling (Wu et al, 2021).…”
Section: Sirtuin Pathwaysmentioning
confidence: 99%
“…SIRT6 attenuates DIC by upregulating endogenous antioxidant levels and attenuating apoptosis ( Wu et al, 2021 ). The latter is achieved by SIRT6 interaction with p53, which leads to the repression of p53 transcription and binding to the Fas/FasL promotor region to reduce apoptotic signaling ( Wu et al, 2021 ). SIRT6 also enhances GATA-4 chromatin binding capacity via TIP60 recruitment, counteracting DOX-induced apoptosis ( Peng et al, 2020 ).…”
Section: Mirnas Involved In the Inhibition Of Pro-survival Signaling ...mentioning
confidence: 99%
“…Indeed, the chemotherapy of breast cancer, lymphoma, leukaemia, and sarcoma by anthracyclines reduces left ventricular mass in patients [ 73 , 74 , 75 , 76 , 77 ]. Doxorubicin, when administered to healthy laboratory animals per se reduces heart weight in males [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] but not in females [ 89 ]. In addition, doxorubicin has a dose-dependent pro-arrhythmic potential mostly due to oxidative stress [ 90 ].…”
Section: Conditions Leading To Myocardial Atrophy and Incidence Of Ca...mentioning
confidence: 99%